Description of nine new centipede species from Amazonia and related matters on Neotropical geophilomorphs (Chilopoda: Geophilomorpha) - Pereira, Luis Alberto (1995)
Fil: Pereira, Luis Alberto. Facultad de Ciencias Naturales y Museo; Universidad Nacional de La Plata